1990
DOI: 10.2190/lykr-7vhp-yjem-mkm2
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Depression in Primary Care Clinics: The CES-D and the BDI

Abstract: The present study was undertaken to examine the utility of the Center for Epidemiological Studies-Depression (CES-D) scale and the Beck Depression Inventory (BDI) as screening instruments for primary care clinic patients. We examined: 1) patients' willingness to complete the scales; 2) the level of agreement between the screening instruments and DSM-III diagnosis of Major Depressive Episode, based on the NIMH Diagnostic Interview Schedule (DIS); 3) the effect on detection rates of raising the cut-off score for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
327
4
4

Year Published

2001
2001
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 537 publications
(351 citation statements)
references
References 46 publications
16
327
4
4
Order By: Relevance
“…Use of a cutoff of 16 on the CES-D may also be considered a limitation, as there is no consensus in the literature on the most valid cutoff for depression screening. A cutoff of 16 is most widely used, but has been criticized for being too low, leading to a high number of false positives and low PPV values [17,18,20,22]. Still, while workers in this study who scored above 16 may not have had clinical depression, we have shown that even subthreshold depressive symptoms are related to poorer RTW outcomes, a finding that is consistent with other research demonstrating a relationship between subthreshold depression and functional impairment [49][50][51].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Use of a cutoff of 16 on the CES-D may also be considered a limitation, as there is no consensus in the literature on the most valid cutoff for depression screening. A cutoff of 16 is most widely used, but has been criticized for being too low, leading to a high number of false positives and low PPV values [17,18,20,22]. Still, while workers in this study who scored above 16 may not have had clinical depression, we have shown that even subthreshold depressive symptoms are related to poorer RTW outcomes, a finding that is consistent with other research demonstrating a relationship between subthreshold depression and functional impairment [49][50][51].…”
Section: Discussionsupporting
confidence: 87%
“…This cutoff has been shown to be an indicator of significant depressive symptomatology [15]. The sensitivity and specificity of this cutoff for detecting depressive disorders has been demonstrated to range from 64 to 100 % and 39 to 94 %, respectively, in community, primary care, and pain populations [16][17][18][19][20][21][22]. The positive predictive value (PPV) and negative predictive value (NPV) of this cutoff have ranged from 14 to 63 % [16][17][18][19][20][21] and 78 to 99 % [17,[19][20][21], respectively.…”
Section: Main Study Variablesmentioning
confidence: 99%
“…Several cross-sectional studies on this topic have shown adequate validity of questionnaire measures, indicating that a high score on such a selfrating scale is the strongest predictor of the presence of a depression diagnosis (Zich et al, 1990;Becht et al, 2001). However, since repeated assessments of depressive symptoms may predict depression better than a single determination, it would be of substantial relevance to establish the additional value of multiple questionnaire assessments over a single measurement.…”
Section: Introductionmentioning
confidence: 99%
“…However, since repeated assessments of depressive symptoms may predict depression better than a single determination, it would be of substantial relevance to establish the additional value of multiple questionnaire assessments over a single measurement. Moreover, knowing the predictive power of multiple questionnaire assessments for the presence of a depression diagnosis would be of significance for epidemiological investigations using depressive symptoms as predictors of health, as well as for depression assessment in clinical practice (Zich et al, 1990). Regarding the former issue, an example showing the potential importance of repeated assessment of depressive symptoms is a recent study in which it was demonstrated that while a single measurement of a depressive state did not predict risk for cancer, multiple measurements did show an enhanced risk of future cancer development in persons scoring consistently high on a measure of depressive symptoms (Penninx et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Patient inclusion criteria comprised: (1) angiographically-documented coronary artery disease (defined as >50% stenosis in an epicardial coronary artery on selective coronary angiography [34]) or systolic heart failure (heart failure admission and an ejection fraction < 40%), (2) co-morbid clinically relevant depression (determined by a score of greater than or equal to 16 on the Center for Epidemiological Studies Depression Scale (CES-D) [35]), and (3) able to complete questionnaires in written English.…”
Section: Patientsmentioning
confidence: 99%